ELYSIUMGATE: Non-Fungible Tokens (NFTS) for Event Perfection - Babu, G Prakash; Bal, Ayush; Singh, Purvi; Das, Abhiraj; A.S, Akshara (Leading the Charge: A Guide to Management, Entrepreneurship and Technology in the Dynamic Business Landscape Edition 1, 2025)
In recent years, blockchain technology has witnessed significant attention and adoption across various industries due to its potential to revolutionize traditional systems. Non-Fungible Tokens (NFTs), a unique form of digital asset authenticated and stored on a blockchain, have emerged as a novel application within this domain. This paper proposes ELYSIUMGATE, a conceptual framework that harnesses NFTs to enhance the organization and execution of events. By leveraging blockchain’s immutability, transparency, and decentralized nature, ELYSIUMGATE aims to address key challenges associated with event management, including ticketing, authentication, and engagement. This research explores the technical architecture of ELYSIUMGATE, its potential benefits, and implications for event organizers, participants, and stakeholders. Additionally, it discusses potential risks and limitations associated with implementing NFTs in event management. Through a comprehensive analysis, this paper demonstrates how ELYSIUMGATE can contribute to achieving event perfection by ensuring trust, security, and efficiency in event organization and execution.